RETRACTION: Analisis Fungsi Harian Serambi Indonesia pada Masyarakat Desa Doy Kecamatan Ulee Kareng Kota Banda Aceh - AK Jailani; Yan Hendra; Ribut Priadi (JURNAL SIMBOLIKA: Research and Learning in Communication Study (E-Journal), 2020)
RETRACTION TO:Jailani, A., Hendra, Y., & Priadi, R. (2020). RETRACTION: Analisis Fungsi Harian Serambi Indonesia pada Masyarakat Desa Doy Kecamatan Ulee Kareng Kota Banda Aceh. JURNAL SIMBOLIKA: Research and Learning in Communication Study, 6(2), 96-106. doi:https://doi.org/10.31289/simbollika.v6i2.3635This article has been retracted by the publisher based on the following reason:This is based on the editor that the author has committed acts of violation of publication ethics. The author has published a triple publication by submitting the same article to one journals before and one journal after. The author admits that he forgot to have submitted the same article to another journal. This article also has published in the1. Jurnal Ilmiah Komunikasi CommuniqueJAILANI, A., Hendra, Y., & Priyadi, R. (2020). Analisis Implementasi Fungsi Media Massa Pada Harian Serambi Indonesia. Jurnal Ilmiah Komunikasi Communique, 2(2), 85-93. Retrieved from http://ejurnal.stikpmedan.ac.id/index.php/JIKQ/article/view/282. PERSEPSI: Communication Journal, Vol .3 No. 2, 2020, 103-112, DOI: 10.30596/persepsi.v%vi%i.4447(Analisis Fungsi Harian Serambi Indonesia Pada Masyarakat Desa Doy Kecamatan Ulee Kareng Kota Banda Aceh | Jailani | Persepsi: Communication Journal (umsu.ac.id)One of the conditions of submission of a paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere, and also not considered by another journal. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter, and apologies are offered to readers of the journal that this was not detected during the submission dan publication process.